A new species of Perinereis Kinberg, 1865 (Annelida: Nereididae) and invalidation of two congeners from Western India - Prajapat, Vaishali; Villalobos-Guerrero, Tulio F.; Vachhrajani, Kauresh D. (Zootaxa, 2023)
A new Perinereis Group 2 species is described from the hard clayey mudflats of Gulf of Khambhat, Gujarat, India. Perinereis khambhatiensis sp. n. is characterized by having two bar-shaped paragnaths on area VI of proboscis and dorsal ligules not greatly expanded in posterior parapodia. The species can mainly be distinguished from the morphologically similar species P. aibuhitensis (Grube, 1878), P. singaporiensis (Grube, 1878), and P. vancaurica (Ehlers, 1868) by the ridge pattern of areas VI-V-VI, the type of bars on area VI, and the number and distribution of paragnaths chiefly on areas III, IV, and VII–VIII. Two Indian Perinereis varieties originally described from near Gujarat, P. vancaurica var. indica (Bhatt & Bal, 1966) and P. nuntia var. bombayensis (Bhatt & Bal, 1966) are regarded as invalid. Comments on the diagnostic features of species belonging to Perinereis Group 2 are provided and included in a comparative synoptic table to distinguish species. An identification key of species of Perinereis in the ‘aibuhitensis’ group is also provided.